Dysregulated autoantibodies targeting AGTR1 are associated with the accumulation of COVID-19 symptoms - Dennyson Leandro M. Fonseca; Maj Jäpel; Michael Adu Gyamfi; Igor Salerno Filgueiras; Gabriela Crispim Baiochi; Yuri Ostrinski; Gilad Halpert; Yael Bublil Lavi; Elroy Vojdani; Thayna Silva-Sousa; Júlia Nakanishi Usuda; Juan Carlo Santos e Silva; et al. (npj Systems Biology and Applications)
Abstract Coronavirus disease 2019 (COVID-19) presents a wide spectrum of symptoms, the causes of which remain poorly understood. This study explored the associations between autoantibodies (AABs), particularly those targeting G protein-coupled receptors (GPCRs) and renin‒angiotensin system (RAS) molecules, and the clinical manifestations of COVID-19. Using a cross-sectional analysis of 244 individuals, we applied multivariate analysis of variance, principal component analysis, and multinomial regression to examine the relationships between AAB levels and key symptoms. Significant correlations were identified between specific AABs and symptoms such as fever, muscle aches, anosmia, and dysgeusia. Notably, anti-AGTR1 antibodies, which contribute to endothelial glycocalyx (eGC) degradation, a process reversed by losartan, have emerged as strong predictors of core symptoms. AAB levels increased with symptom accumulation, peaking in patients exhibiting all four key symptoms. These findings highlight the role of AABs, particularly anti-AGTR1 antibodies, in determining symptom severity and suggest their involvement in the pathophysiology of COVID-19, including vascular complications.